Chitosan/mesoporous silica hybrid aerogel with bactericidal properties as hemostatic material. (5th January 2021) - Wang, Yingfeng; Yin, Maoli; Zheng, Xianhong; Li, Wei; Ren, Xuehong
Graphical abstract: Highlights: Siloxane aerogels contain MSSNPs and chitosan have been prepared successfully. After combined with MSSNPs, the antithrombogenic activity of aerogel was improved. Aerogel-10-Cl showed effective antimicrobial properties against bacteria. Abstract: A N- halamine precursor monomer, (3-acrylamidopropyl) trimethylammonium chloride (APTMAC) was attached onto mesoporous silica. The hydrogel of chitosan and mesoporous silica-supported N- halamine precursors (MSSNPs) was prepared with γ-chloropropyl-triethoxysilane (CPTES) as the cross-linking agent. A porous three-dimensional microstructure of the siloxane aerogels with low density and high porosity was obtained through lyophilization. After chlorination, the aerogels showed potent bactericidal activities against 100% of S. aureus (7.44 log) and E. coli O157:H7 (7.02 log) within 30 min. Compared with traditional hemostatic materials (pledget and bandage), siloxane aerogels displayed good liquid retention rate and hemostatic properties. Erythrocytes and platelets showed good adhesion properties on the surface of the aerogels. The N- halamine-based aerogels showed good bactericidal and hemostatic properties, which have potential application for wound dressings.